Investigating EFL Higher Education Learners on Essay Writing Skills - Samsul Amri (Journal of Education and Culture (JEC), 2021)
The purpose of this study was to see how good the students were at writing essays. It was organized as a survey project, with selected respondents from the fourth semester of the English Study Program FKIP – Universitas Islam Indragiri (UNISI) Tembilahan. They were given the assignment to write an essay. Format, mechanics, content, organization, and sentence structure were all evaluated assigns. The data analysis findings indicate that the learners' skill in each area of writing was incredibly diverse. Some learners were able to attain the highest conceivable score, while others were not. The data revealed that five learners (25%) had a very outstanding rating, twelve learners (60%) received a good category, and three learners (15%) received a sufficient rating. Altogether, their proficiency ranged from adequate to excellent. They are encouraged to boost their skills in order to achieve better outcomes.